Changes in Prescribing Symptomatic and Preventive Medications in the Last Year of Life in Older Nursing Home Residents - van der Meer, Helene G.; Taxis, Katja; Pont, Lisa G. (Frontiers in Pharmacology, 2018)
Background At the end of life goals of care change from disease prevention to symptomatic control, however little is known about the patterns of medication prescribing at this stage. Objectives To explore changes in prescribing of symptomatic and preventive medication in the last year of life in older nursing home residents. Methods A retrospective cohort study was conducted using pharmacy medication supply data of 553 residents from 16 nursing home facilities around Sydney, Australia. Residents received 24-hour nursing care, were aged ≥ 65 years, died between June 2008 and June 2010 and were using at least one medication one year before death. Medications were classified as symptomatic, preventive or other. A linear mixed model was used to compare changes in prescribing in the last year of life. Results 68.1% of residents were female, mean age was 88.0 (SD 7.5) years and residents used a mean of 9.1 (SD 4.1) medications one year before death. The mean number of symptomatic medications per resident increased from 4.6 medications one year before death to 5.1 medications at death [95% CI 4.4-4.7 to 5.9-5.2, P=0.000], while preventive medication decreased from 2.0 to 1.4 medications [95% CI 1.9-2.1 to 1.3-1.5, P=0.000]. Symptomatic medications were used longer in the last year of life, compared to preventive medications (336.3 days [95% CI 331.8-340.8] versus 310.9 days [95% CI 305.2-316.7], P=0.000). Conclusions Use of medications for symptom relief increased throughout the last year of life, while medications for prevention of long-term complications decreased. But changes were slight and clinical relevance can be questioned